2010
DOI: 10.1039/c0dt00692k
|View full text |Cite
|
Sign up to set email alerts
|

Structural, MALDI-TOF-MS, Magnetic and Spectroscopic Studies of New Dinuclear Copper(ii), Cobalt(ii) and Zinc(ii) Complexes Containing a Biomimicking μ-OH bridge

Abstract: The Py(2)N(4)S(2) octadentate coordinating ligand afforded dinuclear cobalt, copper and zinc complexes and the corresponding mixed metal compounds. The overall geometry and bonding modes have been deduced on the basis of elemental analysis data, MALDI-TOF-MS, IR, UV-vis and EPR spectroscopies, single-crystal X-Ray diffraction, conductivity and magnetic susceptibility measurements. In the copper and zinc complexes, a μ-hydroxo bridge links the two metal ions. In both cases, the coordination geometry is distorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…4,[17][18][19] The electronic properties of these metal systems are determined by the isotropic exchange interaction, which couples the two individual electron spins (S = 1/2) to yield singlet (S = 0) and triplet (S = 1) states, and other interactions such as anisotropic and antisymmetric exchange and dipolar magnetic coupling. 4,[17][18][19] The electronic properties of these metal systems are determined by the isotropic exchange interaction, which couples the two individual electron spins (S = 1/2) to yield singlet (S = 0) and triplet (S = 1) states, and other interactions such as anisotropic and antisymmetric exchange and dipolar magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[17][18][19] The electronic properties of these metal systems are determined by the isotropic exchange interaction, which couples the two individual electron spins (S = 1/2) to yield singlet (S = 0) and triplet (S = 1) states, and other interactions such as anisotropic and antisymmetric exchange and dipolar magnetic coupling. 4,[17][18][19] The electronic properties of these metal systems are determined by the isotropic exchange interaction, which couples the two individual electron spins (S = 1/2) to yield singlet (S = 0) and triplet (S = 1) states, and other interactions such as anisotropic and antisymmetric exchange and dipolar magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Among the vast number of studies on paramagnetic transition metal ion complexes, the study of dinuclear Cu(II) compounds (S = 1/2 spin pair) has been essential in the development of molecular magnetism. 4,[17][18][19] The electronic properties of these metal systems are determined by the isotropic exchange interaction, which couples the two individual electron spins (S = 1/2) to yield singlet (S = 0) and triplet (S = 1) states, and other interactions such as anisotropic and antisymmetric exchange and dipolar magnetic coupling. 20 The isotropic exchange interaction (H ex = −JS 1 •S 2 ) splits the singlet from the triplet state of the dimer by an energy amount J, whereas the remaining interactions can remove the three-fold degeneration of the triplet state even in zero magnetic field (ZFS).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear how the bridging topology determines the antiferro or ferromagnetic nature of the interaction. 26,37,39,47,[49][50][51][52] Additional interest in Co(II) dinuclear complexes is due to their presence in metallohydrolases involved in the hydrolysis of peptide bonds (e.g. in methionine aminopeptidase) and, hence, their potential use as therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…19 The most common experimental techniques for characterising the electronic and magnetic properties of high spin Co( ii ) ions are spectroscopic methods such as UV-vis absorption, magnetic circular dichroism, paramagnetic nuclear magnetic resonance, electron paramagnetic resonance (EPR), and electron-nuclear double resonance, and magnetic techniques such as magnetic susceptibility and magnetisation measurements. 20–40 Characterisation of high spin Co( ii ) ion complexes in different coordination environments with these techniques showed that they present g-values for the S = 3/2 multiplet in the range of 2.1–2.8, and zfs usually greater than 50 cm −1 for hexacoordinated compounds, between 20–50 cm −1 for pentacoordinated compounds and less than 13 cm −1 for tetracoordinated compounds, 41 although some exceptions have been reported. 42–46 Furthermore, the exchange interactions that couple mononuclear Co( ii ) centres in extended lattices are usually below ∼3 cm −1 , and hence usually not detected or poorly discriminated with the most usual experimental techniques, with the only exception being EPR.…”
Section: Introductionmentioning
confidence: 99%
“…Following our research interest on the design of new emissive compounds [20,[24][25][26][27] and metal complexes [28][29][30], in this work, the photophysical properties of another symmetric probe L, with two naphthalene units in the extreme as well, was described together with its ) were mixed in absolute ethanol. After 4h, the solvent was partially removed to ca.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%